A Study on Mandatory Disclosure Requirement of Genetic Resources - Youngmo Kim (Journal of Intellectual Property)
At the 63rd WIPO General Assembly in 2022, it was decided to hold a diplomatic conference on “disclosure requirements” in 2024. This decision signifies a significant step toward the adoption of disclosure requirement regime as an international standard. Under this circumstance, it is essential that the outcome is a legally precise instrument that is workable for patent offices and users. It is crucial that patent offices can implement the instrument without incurring additional or unreasonable operational costs. Furthermore, it is crucial that innovators (particularly SMEs) can navigate national requirements without uncertainty or financial burden. For the purpose, ⓐthe provisions of the legal instrument have been drafted to function as part of the existing patent system; ⓑThe disclosure requirement must be clear and reasonable to allow patent offices to implement the system easily and without undue burden, and to ensure that applicants are able to meet its requirements; ⓒSanctions must be balanced and take account of the underlying objectives of the instrument to ensure that the system is used appropriately while avoiding chilling effects on innovation; ⓓThis disclosure requirement is required to enhance the efficacy, transparency, and quality of the patent system, and to bring consistency and predictability to disclosure requirements across jurisdictions.